Sudden Cardiac Death due to Coronary Artery Vasculitis in a Patient with Relapsing Polychondritis - Heather Bukiri; Steven M. Ruhoy; Jane H. Buckner (Case Reports in Rheumatology)
Relapsing polychondritis (RP) is a systemic autoimmune disease characterized by relapsing and remitting inflammation of the cartilaginous structures of the ears, nose, tracheobronchial tree, and joints. Diagnosis is challenging due to the heterogeneity of clinical manifestations, the relapsing and remitting nature of the disease, the presence of coexistent diseases in at least one-third of patients, and the lack of a diagnostic blood test. Although RP-associated cardiac disease is the second most common cause of death behind tracheobronchial complications, coronary artery vasculitis is rare. This report describes a case of sudden cardiac death due to vasculitis affecting the coronary arteries in a patient with RP. The pathologic findings included obliterative coronary arteritis with plasma cells and storiform fibrosis, features suggesting that IgG4-related disease (IgG4-RD) may have contributed to the patient’s cardiac disease. The literature on vasculitis and cardiac disease in RP and the possible role of IgG4-RD in this setting is also reviewed. The primary take-home message from this case report is the importance of frequent screening for cardiac disease, regardless of symptoms, in patients with RP. In addition, considering the diagnosis of IgG4-RD in some cases thought to be RP may also be warranted.